2012
DOI: 10.1104/pp.112.208611
|View full text |Cite
|
Sign up to set email alerts
|

Production of Diploid Male Gametes in Arabidopsis by Cold-Induced Destabilization of Postmeiotic Radial Microtubule Arrays      

Abstract: Whole-genome duplication through the formation of diploid gametes is a major route for polyploidization, speciation, and diversification in plants. The prevalence of polyploids in adverse climates led us to hypothesize that abiotic stress conditions can induce or stimulate diploid gamete production. In this study, we show that short periods of cold stress induce the production of diploid and polyploid pollen in Arabidopsis (Arabidopsis thaliana). Using a combination of cytological and genetic analyses, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
146
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(148 citation statements)
references
References 100 publications
2
146
0
Order By: Relevance
“…Growth experiments showed that 2n pollen production is stimulated by environmental factors such as temperature, herbivory, wounding, and water and nutrient stress [43,44]. Plants in their natural habitats experience many of the environmental factors that influence 2n gamete rspb.royalsocietypublishing.org Proc R Soc B 280: 20131708 production in growth experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Growth experiments showed that 2n pollen production is stimulated by environmental factors such as temperature, herbivory, wounding, and water and nutrient stress [43,44]. Plants in their natural habitats experience many of the environmental factors that influence 2n gamete rspb.royalsocietypublishing.org Proc R Soc B 280: 20131708 production in growth experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Dehydration, high salinity, low temperature, and aluminum are reported to destabilize cortical MTs in plants (Schwarzerová et al 2002;Sivaguru et al 2003;Abdrakhamanova et al 2003;Shoji et al 2006;Krtková et al, 2012;Ban et al 2013). Postmeiotic radial MT arrays in Arabidopsis male gametes are depolymerized in response to cold stress (De Storme et al 2012). Proteasome-dependent degradation of SPR1 protein is stimulated in response to high salinity (Wang et al 2011).…”
Section: Signaling Pathwaysmentioning
confidence: 99%
“…Interestingly, wounding was the only treatment that did not affect silique production, suggesting that our leaf wounding treatment may not have been strong enough, nor applied at the appropriate time or location, to affect meiosis or reproduction in general. It is noteworthy, however, that although wounding and herbivory are frequently listed as an environmental stressor influencing unreduced gamete production (see, for example, Ramsey and Schemske, 1998;De Storme et al, 2012;Mason and Pires, 2015), this observation appears to rest entirely on the early work of Kostoff (Kostoff andKendall, 1929,1930;Kostoff, 1933). All three of these studies involved plants with serious and direct damage to flower buds by mites (Kostoff andKendall, 1929,1930) or a virus (Kostoff, 1933).…”
Section: Environmental Effectsmentioning
confidence: 99%
“…The most frequently cited method of inducing unreduced gametes through alteration of environmental conditions is the cycling of hot and cold temperatures (Mason et al, 2011;De Storme et al, 2012). This approach has been used extensively by potato breeders to produce and introgress desirable genes from diploid into tetraploid lineages (Dewitte et al, 2012).…”
Section: Introductionmentioning
confidence: 99%